PENGARUH NAUNGAN DAN PEMBERIAN KIESERIT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN NILAM (Pogostemon cablin Benth.) PADA MEDIUM GAMBUT - Anis Tatik Maryani; Gusmawartati Gusmawartati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Plants patchouli (Pogostemon cablin Benth.) is one of the essential oil producing plants that are important, foreign exchange accounted for more than 50% of Indonesia's total exports of essential oils. Indonesian patchouli oil is also the largest supplier in the world market with a contribution of 80- 90%. To obtain essential oils that have a yield of patchouli oil and the high alcohol content, it is necessary to consider several factors namely culture technology, climatic factors, especially rainfall, land (topography or shape of the region, elevation) and market opportunities. This research aims to determine the effect of shade and provision of kieserite on crop growth and production of patchouli. The design used in this research is to Plots Separated (Split Plot Design) with the main plot is shaded and the subplot is provision of kieserite. As the main plot of shaded of two levels: N1 = shade with light intensity 50% and N2 = without shade. As a subplot is the awarding of kieserite which consists of three levels P1 = 3,13 g / polybag, P2 = 6,25 g / polybag, P3 = 9,39 g / polybag. The research results obtained are effect of shade and provision of kieserite on crop growth and production of patchouli. Based on the results of the study showed a higher increase of girth increment, the number of secondary branches, number of leaves, canopy dry weight, root dry weight and growth rate relative to the provision of various doses of Kieserite and shade with light intensity 50% and kieserite dose 9,39 g / polybag with no shade showed a higher increase on levels of patchouli essential oils in plants.